THE EFFECT OF THE RELATIONSHIP BETWEEN THE INDICATORS OF THE SUSTAINABLE GROWTH GAP IN IMPROVING THE QUALITY OF PROFITS IN COMMERCIAL BANKS - Ali Karim Mohammed Kuba (Scholar Express Journals, 2022)
The purpose this study to measure and analyze the impact of the relationship between the indicators of the growth of the permanent gap, the continuity of accounting profits and the improvement of performance for a sample of commercial banks listed in the Iraq Stock Exchange, The researchers used the indicators of the permanent growth gap consisting of actual growth and sustainable growth using the model (Ross, 2007, 2008) as a measure to measure the impact of growth on returns, profits and property rights. The researchers reached the most important conclusions, which are: There is a decrease in the profit distribution ratios in the Bank of Baghdad and the Iraqi Islamic Bank, compared to a clear fluctuation of profits in the United Investment Bank, which reflects the high risk, with a relative fluctuation of returns in the Bank of Baghdad and the United Investment Bank in exchange for a relative stability of returns in the Islamic Bank of Iraq. The researchers came up with the most important recommendations The commercial banks, the research sample, should invest their internal funds in a better way in order to increase the financial returns and its reflection on the banks’ growth in the future
Keywords: SGRG; AGR; SGR; Commercial banks